MEDIA DASAR LIMBAH DAUN KAKAO UNTUK PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Umrah; Saparudin, Saparudin; Yuniati, Eny; Ananda, Meryany (Biology Department, Mathematics and natural science, Tadulako University, 2023)
Cocoa leaf wastes as a basic medium are the nutrition that needed for the growth of white oyster mushroom mycelium (Pleurotus ostreatus). The objectives of this study were determine the cocoa leaf wastes as a basic medium for the growth of white oyster mushroom mycelium and the dosage of basic medium to encourage the best fungal growth. This research was designed in a Completely Randomized Design (CRD), consisting of seven treatments and three replications, namely P1 (Basic Media of 100% cocoa leaf waste), P2 (Basic Media 90% + Suplement 10%), P3 (Basic Media 80% + Suplement 20 %), P4 (Basic Media 70% + Suplement 30%), P5 (Basic Media 60% + Suplement 40%), P6 (Basic Media 50% + Suplement 50%), P7 (Sawdust 70%, 20% rice bran + flour corn 10%). The method that used in this study were media preparation, drying, grinding and formulation. The parameters that observed were the basic media, microscopic characteristics of hyphae, mycelium growth curve and macroscopic characteristics of colonies. The results of P1 and P7 showed the best growth for mycelium, observation of mycelium growth were done every 3 days. The isolation stage was carried out on Potato Sucrose Agar (PSA) media, the results obtained that P1 was 0,1 x 1012 CFU/g, P2 was 0,4 x 1012 CFU/g, P3 was 0,3 x 1012 CFU/g, P4 as much as 0,7 x 1012 CFU/g, P5 as much as 0,6 x 1012 CFU/g, P6 as much as 0,4 x 1012 CFU/g, P7 as much as 2,4 x 1012 CFU/g, respectively. Cocoa leaf waste are potentially as a growth medium for mycelium of white oyster mushroom.